High positioning accuracy in GNSS systems and receivers - Marco Lisi (mediaGEO soc. coop., 2018)
In the last few months we have been witnessing a remarkable (and, to some extent, surprising) increase of interest for GNSS high accuracy positioning, involving both systems and receivers. In particular, this growing demand for increased positioning accuracy is evident for mass-market applications, in areas such as: IoT tracking devices, wearable tracking devices, automotive, UAV's; Robotic vehicles. Several GNSS augmentation methods have been developed over the years, aiming at improving the navigation system performance not only in terms of positioning accuracy, but also in terms of reliability, availability and sometime integrity.